HUBUNGAN KONTRASEPSI ORAL DAN KANKER PAYUDARA DI RSUD RD.MOEWARDI SURAKARTA - Elok Dwi Prastiwi; Yuli Kusumawati (Jurnal Berita Ilmu Keperawatan, 2009)
The incidence of breast cancer has been increasing among women in developed and developing countries. Oral contraceptive is the commonest type of contraceptive among women of reproductive age This study employed case control design. The target population was women of reproductive age. The source population was women of reproductive age who were hospitalized for breast cancer at the surgical ward at the Dr. Moewardi Hospital. A sample of 40 breast cancer case and another of 40 controls were selected at random from the source population. The dependent variable under study was the incidence of breast cancer. The independent variable under study was oral contraceptive use. The confounding factors to be controlled for included age, age at menarche and family history. Data was analyzed by multiple logistic regression model, run under SPPS v 16 program. The results showed an increased risk of breast cancer twice as many among oral contraceptive users as those non users, but this relationship was statiscallu non significant (OR=2.20; CI95% 0.78 to 6.21, p=0,138). This estimate has accounted for the effects of age, age at menarche and family history.